Chocolate cakes preference using ranking fuzzy numbers (Keutamaan kek coklat menggunakan pemangkatan nombor kabur) - Lazim Abdullah,; Nashrah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2011)
Ranking is one of the widely used evaluation methods in deciding the best food that is available in today’s competitive market. However, ranking is not always a straight forward process especially when dealing with fuzzy linguistic of multi-attributes evaluation. This paper presents a method of ranking fuzzy numbers to ranking of four selected chocolate cakes according to five attributes. Data in the form of linguistic terms from a sensory experiment were collected from thirty judges in Terengganu. Judges evaluate the chocolate cakes according to five major sensory attributes, i.e. colour, sweetness, texture, humidity and flavour on a 5-point linguistic terms. Sensory data were transformed into fuzzy numbers using linguistic values. Decisions are made based on the centroid point ( x(A), y(A) ), where x(A)and y(A) indicate the distance values from the centroid point to original point on horizontal axis and vertical axis for a fuzzy number. These points permit to characterise the evaluation behaviour of the attributes of chocolate cakes. It is found that no single cake was dominating the first ranking in all the five attributes. The analyses of sensory evaluation using a method of ranking fuzzy numbers successfully ranked the chocolate cakes with multi-attributes.